1995
DOI: 10.1177/00220345950740010401
|View full text |Cite
|
Sign up to set email alerts
|

A Compilation of Partial Sequences of Randomly Selected cDNA Clones from the Rat Incisor

Abstract: The formation of tooth organs is regulated by a series of developmental programs. We have initiated a genome project with the ultimate goal of identifying novel genes important for tooth development. As an initial approach, we constructed a unidirectional cDNA library from the non-calcified portion of incisors of 3- to 4-week-old rats, sequenced cDNA clones, and classified their sequences by homology search through the GenBank data base and the PIR protein data base. Here, we report partial DNA sequences obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Density scans of fluorographs for proteins in the enamel organ at 1 or 10 min after single injections of radioactive methionine and tyrosine have shown that intensity of radiolabeling of this 57-kD protein was the highest next to the 27-kD protein, which corresponds to amelogenin (Smith and Nanci 1996). Matsuki et al (1995) constructed an unidirectional cDNA liberally from the growing end of the rat incisor, sequenced cDNA clones, classified their sequence, and showed that, among the enamel matrix-specific genes, the most redundant mRNAs next to amelogenin were for ameloblastin. These results raise the possibility that ameloblastin corresponds to the sulfated glycoprotein demonstrated by Smith et al (1995).…”
Section: Discussionmentioning
confidence: 99%
“…Density scans of fluorographs for proteins in the enamel organ at 1 or 10 min after single injections of radioactive methionine and tyrosine have shown that intensity of radiolabeling of this 57-kD protein was the highest next to the 27-kD protein, which corresponds to amelogenin (Smith and Nanci 1996). Matsuki et al (1995) constructed an unidirectional cDNA liberally from the growing end of the rat incisor, sequenced cDNA clones, classified their sequence, and showed that, among the enamel matrix-specific genes, the most redundant mRNAs next to amelogenin were for ameloblastin. These results raise the possibility that ameloblastin corresponds to the sulfated glycoprotein demonstrated by Smith et al (1995).…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization for collagen types I and II was performed exactly as described previously (20) by using sense and antisense murine collagen type I and II cDNA probes (28,40). In brief, paraffin sections prepared as described above were dewaxed in xylene, rehydrated through a series of EtOH solutions of decreasing concentrations, treated with 5 g/ml proteinase K, postfixed in 4% PFA in phosphate-buffered saline (PBS), acetylated in triethanolamine hydrochloride-acetic anhydride, washed in PBS, dehydrated, and air dried.…”
Section: Animalsmentioning
confidence: 99%
“…A 4 kb EcoRI-XhoI fragment of rat EST R47123 25 was radiolabeled with ␣-32 P-dCTP using the random primer synthesis method 26 and was used to screen a phage Uni-ZAP human umbilical vein endothelial cell (HUVEC) cDNA library (Stratagene, La Jolla, CA). 27 Plaque-purified clones were rescued into pBS SK ϩ by in vivo excision and were amplified, and inserts were evaluated by restriction endonuclease digestion and DNA sequence analysis.…”
Section: Cdna Library Screeningmentioning
confidence: 99%